Impact of environmental stress on reproductive development in sweet pepper (Capsicum annuum L.) - Jaafar, Hawa Zulkifli (1995)
This investigation was aimed at determining the impact of environmental stresses such as high temperature, low irradiance and drought on reproductive development in sweet pepper, particularly var. Blue Star. Special attention was given to abscission of the primary and secondary flowers. The role of assimilate accumulation and partitioning and the endogenous growth regulator ethylene in mediating stress effects on flower abscission were investigated. The hypothesis that flower abscission is promoted by these stress factors and that abscission is mediated by increased ethylene production and reduced assimilate partitioning to the flowers was tested.